System implementation stages of the innovative culture development of the future manager of the general secondary educational institution in the magister preparation process - Kozlov, Dmytro (Національний технічний університет "Харківський політехнічний інститут", 2020)
the article is devoted to the description of individual parts of the experimental work, the general purpose of which was to determine the system implementation stages of the innovative culture development of the future manager of general secondary educational institution in the magister preparation process. The innovative culture development process of the future manager of general secondary educational institution in the conditions of the magistracy is described, which includes the following stages: motivational-cognitive, professional-practical, creative-active, professionally relevant.

Cтаття присвячена опису окремих частин експериментальної роботи, загальною метою якої було визначення етапів впровадження системи інноваційної культури майбутнього керівника загальноосвітнього навчального закладу в процесі підготовки магістратури. Описано процес розвитку культури майбутнього керівника загальноосвітнього навчального закладу в умовах магістратури, який включає такі етапи: мотиваційно-пізнавальний, професійно-практичний, творчо-активний, професійно актуальний.
Етапи реалізації системи розвитку інноваційної культури майбутнього керівника закладу загальної середньої освіти в процесі магістерської підготовки
Keywords: experimental work; magister preparation process; експериментальна робота; процес підготовки магістратури